Grow Up Branding Assistance: Improving the Business Competition System of MSME Local Tempe Products in Ponorogo - Aziz Kurniawan; Nizomul Mulki; Muhammad Fajar Hamijar; May Shinta Retnowati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Ponorogo is one of the areas where the majority of people like to consume tempe. Tempe is a local product dish that is favorite of the Ponorogo People. The village of Bangunrejo is one of the villages where many of its residents produce tempe, one of which is Mr. Aji's “Tempe Balap”. Tempe balap still maintains the quality of tempe with a leaf wrapping system, but thus the branding of Tempe Balap is not known by many people. The mentoring program carried out by the service team is aimed at helping the people of Bangunrejo Village in improving MSMEs and improving the quality of sales and competitiveness of the community. The method used is Environmental Scanning (ES) with a Thematic approach. The existence of ES as a management strategy so that it can optimize the potential possessed by partners. The intended partners in this program are Tempe MSMEs in Bangunrejo Village. The results of the mentoring carried out during this program show that the potential possessed by Tempe Balap can be optimized by introducing products massively to the public through the existing product growth up branding so that it has an impact on increasing purchases after the presence of branding labels in tempeh packaging. From this stage of service, strategic factors can emerge to develop the potential of local tempe products, as well as the results of monitoring and evaluation are able to bring out a significant development impact of the profits obtained by Tempe Balap MSMEs.